New Missions and Ambitions for Russian Universities - Jean, Tatiana (International Higher Education, 2013)
President Putin wants five Russian universities in the global TOP 100 by 2020. The quality of training deteriorated during transition period, particularly because of insufficient state funding. Soviet legacy, research activities remain separated from teaching. Student demography is an additional worrying factor today. In spite of three Excellence Initiatives and increasing founding, Russia's road to international leadership seems to be a long one.